Design, synthesis, and biological evaluation of a new series of pyrazole derivatives: Discovery of potent and selective JNK3 kinase inhibitors. (1st September 2022) - Abu Rabah, Reinad R.; Sebastian, Anusha; Vunnam, Srinivasulu; Sultan, Shaista; Tarazi, Hamadeh; Anbar, Hanan S.; Shehata, Mahmoud K.; Zaraei, Seyed-Omar; Elgendy, Sara M.; Al Shamma, Salma A.; Omar, Hany A.; Al-Tel, Taleb H.; et al.
Graphical abstract: Compound 1f JNK3 kinase, IC50 = 97.4 nM (selective) Sub-micromolar IC50 values against nine cancer cell lines WI-38 normal cells, IC50 = 16.84 µM (high selectivity indexes) Inducer of apoptosis and necrosis in RPMI-8226 leukemia cells NanoBRET assay, IC50 = 3.84 µM Weak inhibitor of CYP 2D6, CYP 3A4, and hERG Highlights: Synthesis, biological activities, and in silico studies of new pyrazole derivatives are reported. Compounds 1c, 1f, 1h, 1k, and 1v are the most promising anticancer derivatives. Compounds 1c and 1f are potent and selective inhibitors of JNK3 kinase. Compounds 1c and 1f are weak inhibitors of CYP 2D6, CYP 3A4, and hERG. Modeling studies were performed to explain the binding mode of compound 1f . Abstract: The design, synthesis, and biological activities of a new series of pyrazole derivatives are reported. The target compounds 1a-1w were initially investigated against NCI-60 cancer cell lines. Compounds 1f, 1h, 1k, and 1v exerted the highest anti-proliferative activity over the studied panel of cancer cell lines. Compound 1f showed the most potent activity, and it is more potent than sorafenib in 29 cancer cell lines of different types and more potent than SP600125 against almost all the tested cancer cell lines. It also exerted sub-micromolar IC50 values (0.54–0.98 µM) against nine cell lines. Moreover, the 23 target compounds were tested against Hep3B and HepG2 hepatocellular carcinoma cell lines, of which compounds 1b, 1c, and 1h showed the strongest anti-proliferative activity. The most potent anticancer compounds (1b, 1c, 1f, and 1h ) demonstrated a high selectivity towards cancer cells vis-à-vis normal cells. Compounds 1f and 1h induced apoptosis and mild necrosis upon testing against RPMI-8226 leukemia cells. Kinase profiling of this series led to the discovery of two potent and selective JNK3 inhibitors, compounds 1c and 1f with an IC50 values of 99.0 and 97.4 nM, respectively. Both compounds showed a good inhibitory effect against JNK3 kinase in the whole-cell NanoBRET assay. This finding was further supported through molecular modeling studies with the JNK3 binding site. Moreover, compounds 1c and 1f demonstrated a very weak activity against CYP 2D6, CYP 3A4, and hERG ion channels.